Test for Trade-Off between Return and Risk: Empirical Evidences from Chinese stock market - LI, JIARU (2017)
Abstract The Capital Asset Pricing Model (CAPM) is one of the most significant theories of modern finance and the cornerstone of all other asset pricing theories. It has been fifty or sixty years since this model established in 1952. Chinese scholars have made number of relevant empirical test for the applicable of CAPM in recent years, but the results are different. The objective of this paper is to test for trade-off between return and risk and research whether the Capital Asset Pricing Model (CAPM) is applicable to Chinese securities market, if not, what is the reason. This paper exam Capital Asset Pricing Model (CAPM) in China basing on monthly stock returns from 150 companies in Shanghai stock market for the period of 1/1/2012 to 12/31/2016. It concludes that in the Chinese stock market, there is insufficient evidence to proof the basic opinion that high risk is associated with high levels of return. What is more, beta is not related to excess returns, which also prove that CAPM is not applicable to Chinese securities market. Finally, interpretation of results and some suggestions are given.